Determinan perilaku makan sehat dan kecenderungan makan sehat pada mahasiswa - Hartika, Andi Yuniarsy; Wahyudi, Donny Tri; Damayanti, Ana; Iskandar, Ayuk Cucuk (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: As people graduate from high school and go on to college or the workforce, shift from youth to young adulthood signifies a transformation in their lives. They start to have more autonomy over their choices, including choosing their foods.Objectives: This study aimed to determine healthy eating habits and its correlation with the likelihood of healthy eating habits among college students Methods: This study is a cross sectional design conducted 384 college students of University of Borneo Tarakan in 2024 with Stratified Random Sampling technique from representative of each faculty. The questionnaire used The Eating Behavior Determinant with Health Belief Model Approach. All items was measured with a 7-point bipolar scale (-3 to 3). Data analysis using the Pearson test.  Results: Predictors that have a significant relationship with The Likelihood of Healthy Eating with R2=0,654 R=0,809 are Self-Efficacy (b 0,46 95% CI 0,38-0,54), Food Intake Status (b 0,22 95% CI 0,15-0,29), Cues To Action (b 0,16 95% CI 0,08-0,25), Perceived Benefits (b 0,13 95% CI 0,06-0,19) and  Understanding the Importance of Healthy Eating (b 0,10 95% CI 0,02-0,19), while that no significant relationship are Perceived Severity (b -0,019, p=0,584), Perceived Vulnerability (b -0,027, p=0,357),  Perceived Barriers (b 0,002, p=0,961), Food Choices (b -0,059, p=0,178) .Conclusion: This study shows that various psychosocial and behavioral factors—including self-efficacy, food intake status, perceived benefits, and cues to action significantly influence healthy eating habits among college students and the Health Belief Model can explain 65,4% of the variation in healthy eating behavior among college students. Practical recommendations include developing campus programs that enhance self-efficacy through healthy food choice skills training.